Negative electrode binder for lithium-ion secondary batteries
Patent Information
- Application Number
- JP2021016412
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-02-04
- Publication Date
- 2025-03-05
- Estimated Expiration
- 2041-02-04
AI Technical Summary
【0015】 本発明によれば、イオン伝導度およびリチウムイオン輸率が高く、充放電サイクルにおけるサイクル耐久性に優れ、放電容量が高いリチウムイオン二次電池を与える負極バインダー、前記負極バインダーを含む負極、前記負極バインダーを含む負極を有するリチウムイオン二次電池、ならびに前記負極バインダーに好適に用いることができるリチウムボレート型カフェ酸ポリマーおよびその製造方法が提供される。
Smart Images

Figure 0007640072000012 
Figure 0007640072000013 
Figure 0007640072000014
Abstract
Description
[Technical field]
[0001] The present invention relates to a negative electrode binder for lithium ion secondary batteries. More specifically, the present invention relates to a negative electrode binder for lithium ion secondary batteries, a negative electrode containing the negative electrode binder, a lithium ion secondary battery having a negative electrode containing the negative electrode binder, and a lithium borate-type caffeic acid polymer suitable for use in the negative electrode binder for lithium ion secondary batteries and a method for producing the same. [Background technology]
[0002] As negative electrode binders for lithium ion secondary batteries, binders made of polymers obtained by polymerizing a negative electrode monomer composition containing a styrene monomer and an ethylenically unsaturated carboxylic acid monomer (see, for example, paragraph
[0016] of Patent Document 1), binders made of thermosetting resins such as polyimide, polyamide, polyamideimide, polyacrylic acid resins, and polymethacrylic acid resins (see, for example, paragraph
[0029] of Patent Document 2), and the like have been proposed.
[0003] In recent years, there has been a demand for the development of negative electrode binders that provide lithium ion secondary batteries that have high ionic conductivity and lithium ion transport number, excellent cycle durability in charge-discharge cycles, and high discharge capacity. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] International Publication No. 2011 / 122297 Brochure [Patent Document 2] JP 2012-124057 A Summary of the Invention [Problem to be solved by the invention]
[0005] The present invention has been made in view of the above-mentioned conventional techniques, and an object of the present invention is to provide a negative electrode binder that provides a lithium ion secondary battery having high ionic conductivity and lithium ion transport number, excellent cycle durability in charge-discharge cycles, and high discharge capacity, a negative electrode containing the negative electrode binder, a lithium ion secondary battery having a negative electrode containing the negative electrode binder, and a lithium borate-type caffeic acid polymer that can be suitably used for the negative electrode binder, and a method for producing the same. [Means for solving the problem]
[0006] The present invention relates to (1) Formula (I):
[0007] [ka]
[0008] [In the formula, R 1 and R 2 are each independently a hydrogen atom, a hydroxyl group, or an alkyl group having 1 to 4 carbon atoms; R 3 is a hydrogen atom or the formula: -OR 4 group (in the formula, R 4 represents a hydrogen atom, an alkyl group having 1 to 6 carbon atoms which may have a halogen atom, or an aryl group having 6 to 12 carbon atoms which may have a halogen atom), A negative electrode binder for a lithium ion secondary battery, comprising a lithium borate-type caffeic acid polymer having a repeating unit represented by (2) A negative electrode for a lithium ion secondary battery, comprising the negative electrode binder for a lithium ion secondary battery according to (1) above. (3) A lithium ion secondary battery having a positive electrode, a negative electrode, and a separator disposed between the positive electrode and the negative electrode, the negative electrode being the lithium ion secondary battery negative electrode according to (2) above. (4) Formula (I):
[0009] [ka]
[0010] [In the formula, R 1 and R 2 are each independently a hydrogen atom, a hydroxyl group, or an alkyl group having 1 to 4 carbon atoms; R 3 is a hydrogen atom or the formula: -OR 4 group (in the formula, R 4 represents a hydrogen atom, an alkyl group having 1 to 6 carbon atoms which may have a halogen atom, or an aryl group having 6 to 12 carbon atoms which may have a halogen atom), A lithium borate type caffeic acid polymer having a repeating unit represented by the formula: (5) Formula (II):
[0011] [ka]
[0012] (In the formula, R 1 and R 2 each independently represents a hydrogen atom, a hydroxyl group, or an alkyl group having 1 to 4 carbon atoms. and lithium borohydride in a solution of the formula: R 4 OH (in the formula, R 4 represents a hydrogen atom, an alkyl group having 1 to 6 carbon atoms which may have a halogen atom, or an aryl group having 6 to 12 carbon atoms which may have a halogen atom),
[0013] [ka]
[0014] [In the formula, R 1 and R 2 is the same as above, and R 3 is a hydrogen atom or the formula: -OR 4 group (in the formula, R 4 represents a group represented by the formula (I) as defined above. A method for producing a lithium borate type caffeic acid polymer having a repeating unit represented by Regarding. Effect of the Invention
[0015] According to the present invention, there are provided a negative electrode binder that provides a lithium ion secondary battery having high ionic conductivity and lithium ion transport number, excellent cycle durability in charge-discharge cycles, and high discharge capacity, a negative electrode containing the negative electrode binder, a lithium ion secondary battery having a negative electrode containing the negative electrode binder, and a lithium borate-type caffeic acid polymer that can be suitably used for the negative electrode binder and a method for producing the same. [Brief description of the drawings]
[0016] [Figure 1] 1 is a graph showing the NMR spectrum of the lithium borate-type caffeic acid polymer obtained in Example 1. [Diagram 2] Graph (a) shows the relationship between 1000 / T and log σ of the lithium borate-type caffeic acid polymer obtained in Example 1, and graph (B) shows the Vogel-Fulcher-Tammann plot of the lithium borate-type caffeic acid polymer obtained in Example 1. [Diagram 3] 1 is a graph showing the measurement results of linear sweep voltammetry of the coin battery obtained in Example 1. [Figure 4] 1 is a graph showing the change in current over time when determining the lithium ion transport number of a lithium borate-type caffeic acid polymer using the coin battery obtained in Example 1. [Diagram 5] 1 is a graph showing (a) the measurement results of cyclic voltammetry of the coin battery obtained in Example 1, and (b) the measurement results of the discharge capacity and charge / discharge efficiency (Coulombic efficiency) of the coin battery obtained in Example 1. [Figure 6] 1 is a graph showing the relationship between the scanning rate and the peak current when cyclic voltammetry is measured using the coin battery obtained in Example 1. [Figure 7]1 is a graph showing EIS spectra before and after cyclic voltammetry measurement of the coin battery obtained in Example 1. [Figure 8] Graph (a) shows the EIS spectrum of the coin battery obtained in Example 1 before cyclic voltammetry measurement, and graph (b) shows the EIS spectrum of the coin battery obtained in Example 1 after cyclic voltammetry measurement. [Figure 9] 2 is a graph showing the measurement results of the discharge capacity and the charge / discharge efficiency (Coulomb efficiency) when the coin battery obtained in Example 1 was repeatedly charged and discharged. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] The present invention will be described in detail based on the embodiments described below, but the present invention is not limited to these embodiments, and various changes and modifications can be made by those skilled in the art within the scope of the technical ideas described in this specification.
[0018] [Lithium borate-type caffeic acid polymer] As described above, the lithium borate type caffeic acid polymer of the present invention has the formula (I):
[0019] [ka]
[0020] [In the formula, R 1 and R 2 are each independently a hydrogen atom, a hydroxyl group, or an alkyl group having 1 to 4 carbon atoms; R 3 is a hydrogen atom or the formula: -OR 4 group (in the formula, R 4 represents a hydrogen atom, an alkyl group having 1 to 6 carbon atoms which may have a halogen atom, or an aryl group having 6 to 12 carbon atoms which may have a halogen atom), The repeating unit has the following structure:
[0021] The lithium borate type caffeic acid polymer of the present invention is a useful compound for a negative electrode binder for lithium ion secondary batteries. By using the lithium borate type caffeic acid polymer of the present invention as a negative electrode binder for lithium ion secondary batteries, the ionic conductivity, lithium ion transport number, and discharge capacity of the lithium ion secondary battery can be increased, and the durability of the lithium ion secondary battery against charging and discharging can be improved.
[0022] In formula (I), R 1 and R 2 R are each independently a hydrogen atom, a hydroxyl group, or an alkyl group having 1 to 4 carbon atoms. 1 and R 2 From the viewpoint of increasing the ionic conductivity and the lithium ion transport number and obtaining a lithium ion secondary battery that is excellent in durability against charging and discharging and has a high discharge capacity, each of them is preferably a hydrogen atom or an alkyl group having 1 to 4 carbon atoms, and more preferably a hydrogen atom.
[0023] In formula (I), R 3 is a hydrogen atom or a group of the formula: -OR 4 group (in the formula, R 4R represents a hydrogen atom or an alkyl group having 1 to 6 carbon atoms which may have a halogen atom, or an aryl group having 6 to 12 carbon atoms which may have a halogen atom). Examples of the halogen atom include a fluorine atom, a chlorine atom, a bromine atom, and an iodine atom. Among the halogen atoms, a fluorine atom and a chlorine atom are preferable, and a fluorine atom is more preferable. Examples of the alkyl group having 1 to 6 carbon atoms which has a halogen atom and is resistant to freezing include a bis(trifluoromethyl)methyl group. Examples of the aryl group having 6 to 12 carbon atoms include a phenyl group, a tolyl group, and a xylyl group, but the present invention is not limited to only these examples. Examples of the aryl group having 6 to 12 carbon atoms and which has a halogen atom include a bis(trifluoromethyl)phenyl group, a pentafluorophenyl group, and the like, but the present invention is not limited to only these examples. R 3 In the formula: -OR 4 group (in the formula, R 4 represents an alkyl group having 1 to 6 carbon atoms which may have a fluorine atom or an aryl group having 6 to 12 carbon atoms which may have a fluorine atom), is preferred, and a hydrogen atom is more preferred.
[0024] The lithium borate type caffeic acid polymer having a repeating unit represented by formula (I) can be, for example, a compound represented by formula (II):
[0025] [ka]
[0026] (In the formula, R 1 and R 2 is the same as above) and lithium borohydride in a solution of the formula: R 4 OH(R 4The caffeic acid compound represented by formula (II) can be prepared by reacting the caffeic acid compound represented by formula (II) in the presence or absence of an alcohol represented by formula (II) (wherein R is the same as above). Lithium borohydride is a compound represented by formula LiBH4. When reacting the caffeic acid compound represented by formula (II) with lithium borohydride, 4 When an alcohol represented by OH is present, the lithium borate-type caffeic acid polymer formed has the formula: -OR 4 Group(R 4 is the same as above), a group represented by the following formula (I) can be introduced.
[0027] In formula (II), R 1 and R 2 The compound in which is a hydrogen atom is caffeic acid, which is available as a bio-based compound and has the advantage of being environmentally friendly.
[0028] The reaction of the caffeic acid compound with lithium borohydride can be carried out by, for example, solution polymerization, bulk polymerization, suspension polymerization, emulsion polymerization, etc., but the present invention is not limited to these examples. Among these methods, from the viewpoint of efficiently preparing the lithium borate-type caffeic acid polymer, the solution polymerization and bulk polymerization are preferred, and the solution polymerization is more preferred.
[0029] The amount of lithium borohydride per mole of caffeic acid compound is theoretically 1 mole.Therefore, the amount of caffeic acid compound per mole of lithium borohydride is also theoretically 1 mole.However, when preparing the lithium borate type caffeic acid polymer of the present invention, the amount of lithium borohydride may be in excess of the amount of caffeic acid compound, or the amount of caffeic acid compound may be in excess of the amount of lithium borohydride.
[0030] When preparing a lithium borate-type caffeic acid polymer by solution polymerization of lithium borohydride and a caffeic acid compound, an organic solvent can be used.
[0031] Examples of the organic solvent include tetrahydrofuran, diethylene glycol dimethyl ether (diglyme), dioxane, diethyl ether, etc., but the present invention is not limited to these examples. These organic solvents may be used alone or in combination of two or more kinds.
[0032] The amount of the organic solvent is not particularly limited as long as it can efficiently react the lithium borohydride with the caffeic acid compound. The amount of the organic solvent is usually preferably about 10 to 50 times the total amount (mass) of the lithium borohydride and the caffeic acid compound.
[0033] The reaction between lithium borohydride and a caffeic acid compound can be carried out, for example, by dissolving the caffeic acid compound in the organic solvent and adding lithium borohydride to the resulting solution of the caffeic acid compound. In this case, it is preferable to add a solution of lithium borohydride dissolved in the organic solvent to the solution of the caffeic acid compound, and it is more preferable to add a solution of lithium borohydride dissolved in the organic solvent to the solution of the caffeic acid compound by dropwise addition. The temperature of the solution of lithium borohydride dissolved in the organic solvent is usually about 0 to 15°C.
[0034] When the lithium borohydride and the caffeic acid compound are reacted, it is preferable to stir the mixture of the lithium borohydride and the caffeic acid compound from the viewpoint of maintaining the reaction system uniform. The atmosphere in which the lithium borohydride and the caffeic acid compound are reacted is not particularly limited and may be the air, but from the viewpoint of avoiding the influence of oxygen contained in the air, it is preferable to use an inert gas such as nitrogen gas or argon gas.
[0035] The reaction temperature between lithium borohydride and the caffeic acid compound is not particularly limited, but is preferably about 0 to 60° C. from the viewpoint of increasing the reaction efficiency. The reaction time between lithium borohydride and the caffeic acid compound varies depending on the amount of the organic solvent used, the reaction temperature, etc., and therefore cannot be determined in general, but is usually about 5 to 50 hours.
[0036] By reacting lithium borohydride with a caffeic acid compound as described above, a reaction mixture containing a lithium borate-type caffeic acid polymer having a repeating unit represented by formula (I) is obtained.
[0037] After the reaction is completed, the obtained lithium borate type caffeic acid polymer can be collected by filtration. The collected lithium borate type caffeic acid polymer may be washed with an organic solvent such as tetrahydrofuran, ethyl acetate, dichloromethane, etc., if necessary. The obtained lithium borate type caffeic acid polymer may be dried, for example, by drying under reduced pressure.
[0038] The average molecular weight of the lithium borate-type caffeic acid polymer of the present invention is not particularly limited, but from the viewpoints of increasing the ionic conductivity and lithium ion transport number when used as a negative electrode binder for a lithium ion secondary battery, improving durability against charge and discharge, and increasing the discharge capacity of the lithium ion secondary battery, it is preferably 800 to 100,000, more preferably 1,000 to 50,000, and even more preferably 1,000 to 10,000.
[0039] In the present invention, the average molecular weight of the lithium borate type caffeic acid polymer means the average molecular weight measured by matrix-assisted laser desorption / ionization-time of flight mass spectrometry (MALDI-TOF-MS). The average molecular weight of the lithium borate type caffeic acid polymer is specifically a value measured based on the method described in the following examples.
[0040] The lithium borate type caffeic acid polymer of the present invention may contain units other than the repeating unit represented by formula (I) within the scope of not impairing the object of the present invention.
[0041] [Negative electrode binder for lithium ion secondary batteries] The negative electrode binder for lithium ion secondary batteries of the present invention contains the lithium borate type caffeic acid polymer. The negative electrode binder for lithium ion secondary batteries of the present invention may be composed of only the lithium borate type caffeic acid polymer, and may contain other binders such as polyimide, polyamide, polyamideimide, poly(meth)acrylic acid, polyvinylidene fluoride (PVDF), 1-methyl-2-pyrrolidone (NMP), polytetrafluoroethylene (PTFE), fluororubber, and ethylene propylene diene rubber, as long as the object of the present invention is not hindered. In addition, the negative electrode binder for lithium ion secondary batteries of the present invention may contain other components such as a solvent, as long as the object of the present invention is not hindered.
[0042] Since the negative electrode binder for lithium ion secondary batteries of the present invention contains the lithium borate-type caffeic acid polymer, by using the negative electrode binder for lithium ion secondary batteries of the present invention in the negative electrode of a lithium ion secondary battery, the ionic conductivity and lithium ion transport number can be increased, durability against charging and discharging can be improved, and the discharge capacity of the lithium ion secondary battery can be increased.
[0043] The negative electrode binder for lithium ion secondary batteries of the present invention can be used by dissolving it in a polar solvent. Examples of polar solvents include water, N-methyl-2-pyrrolidone, and N,N-dimethylacetamide, but the present invention is not limited to these examples. These solvents may be used alone or in combination of two or more. Since the negative electrode binder for lithium ion secondary batteries of the present invention dissolves in water, environmental problems caused by the release of volatile organic compounds into the atmosphere can be avoided by using water as a polar solvent.
[0044] The negative electrode binder for a lithium ion secondary battery of the present invention can be used, like a conventional negative electrode binder, as a binder for binding negative electrode active materials together, or a binder for binding a negative electrode active material and a negative electrode current collector.
[0045] [Lithium-ion secondary battery] The lithium ion secondary battery of the present invention has the same structure as commonly used lithium ion secondary batteries.
[0046] The lithium ion secondary battery of the present invention usually has a positive electrode, a negative electrode, a separator, and an electrolyte. The shape of the lithium ion secondary battery may be, for example, a cylindrical type or a laminated type, but the present invention is not limited to these examples.
[0047] When the lithium ion secondary battery of the present invention is, for example, a CR2025 coin battery, the negative electrode, the separator, and the electrolyte are housed in a case. In the following, an embodiment in which the lithium ion secondary battery is a CR2025 coin battery will be described, but the present invention is not limited to only this embodiment.
[0048] The case used in the CR2025 coin battery is hollow, has an opening, and also serves as a positive electrode container. A lid is provided at the opening of the case, and the lid also serves as a negative electrode lid. A gasket is provided between the case and the lid to maintain an insulating and sealed state between the case and the lid. An electrode and an electrolyte are accommodated in the space between the case and the lid.
[0049] (1) Electrode The electrodes include a positive electrode, a separator, and a negative electrode, arranged in that order. The positive electrode is in contact with the inner surface of the case, and the negative electrode is in contact with the inner surface of the lid.
[0050] [Positive electrode] The positive electrode may be the same as a positive electrode used in a commonly used lithium ion secondary battery, and the present invention is not limited by the composition and structure of the positive electrode.
[0051] The positive electrode can be produced, for example, by mixing a positive electrode active material, a conductive material, and a positive electrode binder in a predetermined ratio, adding to the resulting mixture an appropriate amount of a solvent, and if necessary, activated carbon, a viscosity adjusting additive, and the like, kneading the resulting mixture to prepare a positive electrode composite paste, which is then applied to the surface of a current collector, press-molded if necessary, and dried.
[0052] Representative examples of the positive electrode active material include lithium manganese composite oxides, but the present invention is not limited to these examples. Examples of the conductive material include carbon black such as acetylene black, natural graphite, artificial graphite, and expanded graphite, but the present invention is not limited to these examples.
[0053] Examples of the positive electrode binder include polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), fluororubber, and ethylene propylene diene rubber, but the present invention is not limited to these examples.
[0054] Examples of the solvent include N-methyl-2-pyrrolidone, but the present invention is not limited to these examples.
[0055] Examples of the current collector include copper, aluminum, nickel, silver, tin, indium, magnesium, iron, chromium, molybdenum, and alloys thereof, but the present invention is not limited to these examples.
[0056] The positive electrode 10 can be produced, for example, by mixing a positive electrode active material, a conductive additive, a binder and a solvent to prepare a paste-like positive electrode slurry, applying the positive electrode slurry to one or both sides of a positive electrode current collector, and drying the same.
[0057] [Separator] The separator is used between the positive electrode and the negative electrode. The separator separates the positive electrode and the negative electrode, holds the electrolyte, and forms a path for lithium ions to move between the positive electrode and the negative electrode. The separator may be a foil membrane made of a polyolefin resin such as polyethylene or polypropylene, cellulose, or glass. It is preferable that the thin film has a large number of fine pores formed therein.
[0058] [Negative electrode] The negative electrode binder of the present invention is used for the negative electrode. The negative electrode can be produced, for example, by mixing a negative electrode active material with the negative electrode binder of the present invention, adding a solvent to the resulting mixture to prepare a paste-like negative electrode mixture, applying the negative electrode mixture to the surface of a metal foil collector such as copper, drying it, and optionally subjecting it to hot roll press molding and drying it.
[0059] The amount of the negative electrode binder of the present invention cannot be determined in general because it differs depending on the type of negative electrode active material, etc.; however, from the viewpoints of increasing the ionic conductivity, the lithium ion transport number, and the discharge capacity of the lithium ion secondary battery, and improving the durability of the lithium ion secondary battery against charge and discharge, it is desirable to adjust the content of the negative electrode binder in the negative electrode mixture to preferably 1 to 20 mass %, more preferably 2 to 15 mass %, and even more preferably 3 to 10 mass %.
[0060] Examples of the negative electrode active material include carbonaceous materials such as graphite, carbon fiber, and activated carbon, tin oxide, silicon, and silicon oxide, but the present invention is not limited to these examples. These negative electrode active materials may be used alone or in combination of two or more. Among the negative electrode active materials, silicon is preferred from the viewpoint of increasing the capacity of the lithium ion secondary battery. Silicon may be amorphous silicon or silicon crystallites. Silicon nanoparticles can be used as silicon. Silicon nanoparticles are easily available commercially.
[0061] The solvent is preferably a polar solvent. Examples of the polar solvent include the polar solvents described above. Among the polar solvents, water is preferred. When water is used as the polar solvent, as described above, it is possible to avoid environmental problems caused by the release of volatile organic compounds into the atmosphere, and the negative electrode can be produced at low cost, which has the advantage of improving economic efficiency.
[0062] The negative electrode mixture may contain a conductive assistant as necessary. Examples of the conductive assistant include carbon black such as ethylene black, ketjen black, channel black, furnace black, lamp black, and thermal black, conductive fibers such as carbon fibers and metal fibers, metal powders such as carbon fluoride, copper, and nickel, and organic conductive materials such as polyphenylene derivatives, but the present invention is not limited to these examples. The content of the conductive assistant in the negative electrode mixture is usually preferably 10 mass% or less.
[0063] In addition, the negative electrode mixture may contain an appropriate amount of an inclusion compound, if necessary. The inclusion compound has the property of absorbing gas generated in the battery. Examples of the inclusion compound include cyclodextrins such as α-cyclodextrin, β-cyclodextrin, and γ-cyclodextrin, and crown ethers such as 12-crown-4, 15-crown-5, and 18-crown-6, but the present invention is not limited to these examples. The content of the inclusion compound in the negative electrode mixture is usually preferably about 3 to 10 mass%.
[0064] Examples of the current collector include copper, aluminum, nickel, silver, tin, indium, magnesium, iron, chromium, molybdenum, and alloys thereof, but the present invention is not limited to these examples.
[0065] The negative electrode can be produced, for example, by mixing a negative electrode active material, a conductive assistant, a negative electrode binder and a solvent to prepare a paste-like negative electrode slurry, applying the negative electrode slurry to one or both sides of a current collector, and drying the slurry.
[0066] (2) Electrolyte Examples of the electrolyte include cyclic carbonates such as ethylene carbonate, diethylene carbonate, propylene carbonate, butylene carbonate, and trifluoropropylene carbonate; chain carbonates such as diethyl carbonate, dimethyl carbonate, ethyl methyl carbonate, and dipropyl carbonate; and ether compounds such as tetrahydrofuran, 2-methyltetrahydrofuran, and dimethoxyethane, but the present invention is not limited to these examples. These electrolytes may be used alone or in combination of two or more.
[0067] The lithium ion secondary battery of the present invention uses the negative electrode binder of the present invention in the negative electrode, and therefore the ionic conductivity, lithium ion transport number, and discharge capacity of the lithium ion secondary battery can be increased, and the durability of the lithium ion secondary battery against charging and discharging can be improved.
[0068] When the lithium ion secondary battery of the present invention is, for example, a coin-type battery, the ion conductivity at 51° C. is 10 -3 S / cm or more, a lithium ion transport number of 0.8 or more, high cycle durability in 1000 charge / discharge cycles, an initial discharge capacity of 2000 mAh / g or more (Si weight conversion), and a charge / discharge efficiency of approximately 100% after 100 charge / discharge cycles, so the lithium ion secondary battery of the present invention is remarkably excellent in the maintenance of discharge capacity and durability against charge / discharge. EXAMPLES
[0069] Next, the present invention will be described in detail based on examples, but the present invention is not limited to these examples.
[0070] Example 1 In a 100mL three-necked round-bottom flask, 3mmol (540mg) of caffeic acid and 30mL of tetrahydrofuran were placed at room temperature, and caffeic acid was dissolved in tetrahydrofuran to obtain a light brown solution. While continuously introducing nitrogen gas into the flask, 2.5mL of 2M lithium borohydride (LiBH4) aqueous solution at 0℃ was added dropwise into the flask using a dropping funnel, and the color of the solution in the flask changed to fluorescent yellow, and a suspension was formed.
[0071] The suspension obtained above was left at room temperature for 12 hours to react caffeic acid with lithium borohydride, and the resulting suspension containing lithium borate-type caffeic acid polymer was filtered to remove the solvent and recover the solid matter. In order to remove unreacted compounds, the solid matter was washed with 50 mL of tetrahydrofuran, and then washed with 30 mL of ethyl acetate and 30 mL of dichloromethane, resulting in a viscous substance. The viscous substance was reprecipitated with dehydrated diethyl ether to obtain a yellow powder. The powder obtained above was dried under reduced pressure to recover the lithium borate-type caffeic acid polymer (yield: about 60% by mass).
[0072] The average molecular weight of the lithium borate type caffeic acid polymer obtained above was measured according to the method described below. As a result, the average molecular weight of the lithium borate type caffeic acid polymer obtained above was 2,800.
[0073] [Method for measuring the average molecular weight of lithium borate-type caffeic acid polymer] The average molecular weight of the lithium borate type caffeic acid polymer is the average molecular weight measured by matrix-assisted laser desorption / ionization-time of flight mass spectrometry (MALDI-TOF-MS). More specifically, the average molecular weight of the lithium borate type caffeic acid polymer is the value measured based on the following method.
[0074] 2,5-Dihydroxybenzoic acid was dissolved in N,N-dimethylformamide to a concentration of 10 mg / mL, and 1 μL of the resulting solution was mixed with 3 μL of lithium borate-type caffeic acid polymer to obtain a mixed solution. The mixed solution obtained above was dropped onto a plate, the plate was placed in a sample holder, and a matrix-assisted laser desorption ionization-time of flight mass spectrometer (MALDI-TOF-MS, manufactured by Bruker, product name: UltrafleXtreme (registered trademark), laser: wavelength 337 nmkN2 smart beam laser, pulse energy: 150 μJ) was used to measure in regular reflection mode.
[0075] Example 2 In a 100 mL three-necked round-bottom flask, 2 mmol (360 mg) of caffeic acid and 30 mL of tetrahydrofuran were placed at room temperature, and caffeic acid was dissolved in tetrahydrofuran to obtain a light brown solution. While continuously introducing nitrogen gas into the flask, 2.0 mL of 2 M lithium borohydride (LiBH4) aqueous solution at 0°C was added dropwise into the flask using a dropping funnel, and the color of the solution in the flask changed to fluorescent yellow, and a suspension was formed.
[0076] The suspension obtained above was left at room temperature for 12 hours to react caffeic acid with lithium borohydride, and the resulting suspension containing lithium borate-type caffeic acid polymer was filtered to remove the solvent and recover the solid matter. In order to remove unreacted compounds, the solid matter was washed with 50 mL of tetrahydrofuran, and then washed with 30 mL of ethyl acetate and 30 mL of dichloromethane, resulting in a viscous substance. The viscous substance was reprecipitated with dehydrated diethyl ether to obtain a yellow powder. The powder obtained above was dried under reduced pressure to recover the lithium borate-type caffeic acid polymer (yield: about 60% by mass).
[0077] The average molecular weight of the lithium borate type caffeic acid polymer obtained above was measured according to the method described below. As a result, the average molecular weight of the lithium borate type caffeic acid polymer obtained above was 3,500.
[0078] Example 3 In a 100mL three-necked round-bottom flask, 2mmol (360mg) of caffeic acid and 30mL of tetrahydrofuran were placed at room temperature, and caffeic acid was dissolved in tetrahydrofuran to obtain a light brown solution. While continuously introducing nitrogen gas into the flask, 3.0mL of 2M lithium borohydride (LiBH4) aqueous solution at 0℃ was added dropwise into the flask using a dropping funnel, and the color of the solution in the flask changed to fluorescent yellow, and a suspension was formed.
[0079] The suspension obtained above was left at room temperature for 12 hours to react caffeic acid with lithium borohydride, and the resulting suspension containing lithium borate-type caffeic acid polymer was filtered to remove the solvent and recover the solid matter. In order to remove unreacted compounds, the solid matter was washed with 50 mL of tetrahydrofuran, and then washed with 30 mL of ethyl acetate and 30 mL of dichloromethane, resulting in a viscous substance. The viscous substance was reprecipitated with dehydrated diethyl ether to obtain a yellow powder. The powder obtained above was dried under reduced pressure to recover the lithium borate-type caffeic acid polymer (yield: about 60% by mass).
[0080] The average molecular weight of the lithium borate type caffeic acid polymer obtained above was measured according to the method described below. As a result, the average molecular weight of the lithium borate type caffeic acid polymer obtained above was 5,500.
[0081] Next, the following physical properties of the lithium borate-type caffeic acid polymer obtained above were measured.
[0082] (1) Nuclear magnetic resonance (NMR) The lithium borate-type caffeic acid polymer obtained in Example 1 was measured using a nuclear magnetic resonance measurement device (manufactured by Bruker, product name: Advance II 400 MHz spectrometer) equipped with a BBFO probe and an ATMA probe, using dimethylformamide-d7 as a solvent. 1 H-NMR,11 B-NMR and 13 C-NMR was measured, and the results are shown in Figure 1. Figure 1 is a graph showing the NMR spectrum of the lithium borate-type caffeic acid polymer obtained in Example 1.
[0083] In FIG. 1, (a) shows the lithium borate type caffeic acid polymer 1 1H-NMR spectrum of the lithium borate-type caffeic acid polymer. 11 (c) is a graph showing the B-NMR spectrum. 13 1 is a graph showing a C-NMR spectrum. 11 A quartz tube was used for measuring B-NMR. The peaks shown in Figure 1 are assigned as follows:
[0084] 1 H-NMR (400MHz, DMF-d7) (d / ppm): 7.25(d, Hb), 6.8(s, Hc), 6.7(d, Hd), 6.5(d, He), 6.15(d, Ha)
[0085] 13 C-NMR(d / ppm):176(Cf), 152.5(Ch), 151(Ci), 142.5(Cb), 141(Cg), 126(Cd), 121.5(Ce), 119(Ca), 116(Cc)
[0086] (2) Electrochemical properties [Ionic Conductivity] 150 mg of 1-allyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide (AMImTFSI) and 50 mg of the lithium borate-type caffeic acid polymer obtained in Example 1 were mixed, and the resulting mixture was irradiated with ultrasonic waves for 12 hours while stirring to obtain a mixture having a uniform composition.
[0087] The mixture obtained above was sandwiched between two gold electrode plates in an argon gas atmosphere to a thickness of 2 to 3 cm, and the electrode plates were wrapped in a fluororesin film and sealed. The electrode plates were connected to a temperature regulator, and impedance was measured at frequencies from 0.1 Hz to 1 MHz using an impedance / gain-phase analyzer (manufactured by Solartron Analytical). The ionic conductivity was measured at 3°C intervals in the temperature range of 30 to 60°C using the AC impedance method, using the formula: R = ρL / A (where R is resistance, ρ is the specific resistance of the mixture, L is the thickness of the mixture, and A is the area of the electrode plates (0.25 cm 2 The resistance was measured using the circuit R(QR)(QR(W)). The results are shown in Table 1.
[0088] [Table 1]
[0089] From the results shown in Table 1, the lithium borate type caffeic acid polymer has an ionic conductivity of 1.053 × 10 at 324 K (51 ° C.). -3 Scm -1 This shows that the ionic conductivity is excellent.
[0090] Next, the activation energy was calculated from the Arrhenius plot of 1000 / T vs. logσ. The result is shown in Figure 2(a). The activation energy was also calculated from the Vogel-Fulcher-Tammann plot after measuring the ionic conductivity. The result is shown in Figure 2(b).
[0091] FIG. 2(a) is a graph showing the relationship between 1000 / T and log σ of the lithium borate-type caffeic acid polymer, and FIG. 2(B) is a graph showing the Vogel-Fulcher-Tammann plot of the lithium borate-type caffeic acid polymer.
[0092] From the results shown in FIG. 2, it can be seen that there is a correlation between temperature and activation energy for the lithium borate type caffeic acid polymer.
[0093] [Linear Sweep Voltammetry (LSV)] 150 mg of 1-allyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide (AMImTFSI) was mixed with 50 mg of the lithium borate-type caffeic acid polymer obtained in Example 1, and the mixture was irradiated with ultrasonic waves for 12 hours while stirring to disperse the mixture into a uniform composition, thereby obtaining a mixture. The mixture obtained was used as an electrolyte.
[0094] A CR2025 type coin battery was fabricated in a nitrogen gas atmosphere using a substrate having a diameter of 20 mm, a circular lithium plate having a diameter of 13 mm and a thickness of 1 mm, an electrolyte, a circular steel plate having a diameter of 13 mm, a spring and a lid.
[0095] Linear sweep voltammetry was measured at a scan rate of 10 mV / s using an electrochemical measurement system (Biologic, product number: VSP1190). The oxidative stability was examined at a potential from the open circuit potential (OCP) to 6 V, and the reductive stability was examined at a potential from the open circuit potential (OCP) to 0 V.
[0096] The measurement results of linear sweep voltammetry are shown in Figure 3. Figure 3 is a graph showing the measurement results of linear sweep voltammetry of the coin battery obtained above. From the results shown in Figure 3, it can be seen that the stable potential of the coin battery obtained above is 2.5V.
[0097] [Lithium ion transport number] 150 mg of 1-allyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide (AMImTFSI) was mixed with 50 mg of the lithium borate-type caffeic acid polymer obtained in Example 1, and the mixture was irradiated with ultrasonic waves for 12 hours while stirring to disperse the mixture to a uniform composition, thereby obtaining a mixture. The mixture obtained above was used as an electrolyte.
[0098] In a nitrogen gas atmosphere, a CR2025 type coin battery was fabricated using a substrate having a diameter of 20 mm, a circular lithium plate having a diameter of 13 mm and a thickness of 1 mm, the electrolyte, a circular lithium plate having a diameter of 13 mm and a thickness of 1 mm, a circular steel plate having a diameter of 13 mm, a spring, and a lid.
[0099] A potentiostat (Biologic, product number: VSP) equipped with a frequency response analyzer (Biologic) was used, with a scan rate of 10 mV / s, a frequency of 100 kHz to 10 mHz, and a DC voltage of 0.03 V (vs. Li / Li + ) The change in current over time was measured. The results are shown in Figure 4. Figure 4 is a graph showing the change in current over time when the lithium ion transport number of the lithium borate-type caffeic acid polymer was determined using the coin battery obtained above.
[0100] Next, the formula: t Li+ =[I s (ΔV-I0R0)] / [I0(ΔV-I s R s )] [In the formula, I0 is the initial current (7.164 × 10 -2 A), R0 is the initial resistance (397 Ω), I s is the steady-state current (4.709×10 -2 A), R s indicates steady-state resistance (408 Ω) Based on the Evans-Vincent Bruce equation, the lithium ion transport number (t Li+ As a result, the lithium ion transport number (t Li+ ) was 0.87. This shows that the lithium ion transport number of the lithium borate type caffeic acid polymer obtained above is high due to the movement of lithium ions by boron, and therefore the energy density and charging speed of the lithium ion secondary battery can be increased.
[0101] [Electrochemical properties of graphite-based negative electrodes (1)] A mixture was obtained by mixing 160 mg of graphite, 20 mg of acetylene black, 20 mg of the lithium borate-type caffeic acid polymer obtained in Example 1, and 3 to 4 mL of N-methyl-2-pyrrolidone to a uniform composition.
[0102] The mixture obtained above was pulverized using a pulverizer (manufactured by FRITISCH GmbH, product name: Planetary Micro Mill PULVERISETTE 7) and zirconia beads with a diameter of about 5 mm to obtain a slurry-like electrode material. The electrode material obtained above was applied to a copper foil (thickness: 20 μm) with a doctor blade to a thickness of 100 μm, and dried under reduced pressure at 80° C. for about 12 hours to obtain an electrode.
[0103] The electrode obtained above was hot roll pressed to a thickness of 70 μm using a hot roll press machine (manufactured by Hosen) at a temperature of 80° C. A circular negative electrode plate with a diameter of 13 mm was produced from this electrode.
[0104] In a nitrogen gas atmosphere, a CR2025 type coin battery was fabricated using a substrate having a diameter of 20 mm, a circular lithium plate having a diameter of 13 mm and a thickness of 1 mm, a polypropylene separator having a thickness of 25 μm, a non-aqueous electrolyte (70 μL of a 1 M LiPF6 solution dissolved in a solvent consisting of 50 volume % ethylene carbonate and 50 volume % diethylene carbonate), the negative electrode plate obtained above, a circular steel plate having a diameter of 13 mm, a spring, and a lid, and was left at room temperature for about 12 hours for stabilization.
[0105] Using a potentiostat (Biological, product number: VSM), the cyclic voltammetry of the coin battery was examined at room temperature at potentials of 0.01 to 2.1 V. The results are shown in FIG. 5(a). FIG. 5(a) is a graph showing the measurement results of the cyclic voltammetry of the coin battery obtained above. In FIG. 5(a), the symbol a indicates the cyclic voltammogram of the first cycle, and the symbol b indicates the cyclic voltammogram of the second cycle.
[0106] In addition, when examining cyclic voltammetry, the relationship between the number of cycles and the discharge capacity and charge / discharge efficiency (Coulomb efficiency) was examined. The results are shown in Figure 5(b). Figure 5(b) is a graph showing the measurement results of the discharge capacity and charge / discharge efficiency (Coulomb efficiency) of the coin battery obtained above. In Figure 5(b), the symbol A is a graph showing the discharge capacity, and the symbol B is a graph showing the charge / discharge efficiency.
[0107] From the results shown in Figure 5 (b), the maximum discharge capacity is about 228mAh / g, and the discharge capacity after 1000 cycles of cyclic voltammetry is about 180mAh / g, so the capacity retention rate is about 79%, which means that the battery life is long, and even after 1400 cycles, the charge / discharge efficiency (Coulomb efficiency) is maintained at about 100%, and the discharge capacity is about 150mAh / g or more. Therefore, it can be seen that the lithium borate-type caffeic acid polymer obtained above maintains electrical contact with the active material and maintains binding to the active material even after 1400 cycles.
[0108] Next, the relationship between the scan rate and the peak current when measuring cyclic voltammetry using the coin battery obtained above was examined. The results are shown in Figure 6. Figure 6 is a graph showing the relationship between the scan rate and the peak current when measuring cyclic voltammetry using the coin battery obtained above.
[0109] The results shown in Figure 6 indicate that the diffusion of lithium ions is controlled by the linear relationship between the scan rate and the peak current. The lithium ion diffusion coefficient was calculated based on the Randles-Sevcik equation and was found to be 7.8 × 10 -9 cm 2 This shows that the lithium borate type caffeic acid polymer obtained above has the property of efficiently diffusing lithium.
[0110] [Electrochemical properties of graphite-based negative electrodes (2)] Using the lithium borate type caffeic acid polymer obtained in Example 1, 20 mg of acetylene black was mixed with a mixture of 2 mg of lithium borate type caffeic acid polymer and 178 mg of graphite, a mixture of 4 mg of lithium borate type caffeic acid polymer and 176 mg of graphite, a mixture of 6 mg of lithium borate type caffeic acid polymer and 174 mg of graphite, a mixture of 8 mg of lithium borate type caffeic acid polymer and 172 mg of graphite, a mixture of 10 mg of lithium borate type caffeic acid polymer and 170 mg of graphite, a mixture of 14 mg of lithium borate type caffeic acid polymer and 166 mg of graphite, or a mixture of 20 mg of lithium borate type caffeic acid polymer and 160 mg of graphite, and 3 to 4 mL of water as a solvent was further mixed to obtain a uniform composition, thereby obtaining each mixture.
[0111] The mixture obtained above was pulverized using a pulverizer (manufactured by FRITISCH GmbH, product name: Planetary Micro Mill PULVERISETTE 7) and zirconia beads with a diameter of about 5 mm to obtain a slurry-like electrode material. The electrode material obtained above was applied to a copper foil (thickness: 20 μm) with a doctor blade to a thickness of 100 μm, and dried under reduced pressure at 80° C. for about 12 hours to obtain an electrode.
[0112] The electrode obtained above was hot roll pressed to a thickness of 70 μm using a hot roll press machine (manufactured by Hosen) at a temperature of 80° C. A circular negative electrode plate with a diameter of 13 mm was produced from this electrode.
[0113] In a nitrogen gas atmosphere, a CR2025 type coin battery was fabricated using a substrate having a diameter of 20 mm, a circular lithium plate having a diameter of 13 mm and a thickness of 1 mm, a polypropylene separator having a thickness of 25 μm, an electrolyte (70 μL of a 1 M LiPF6 solution dissolved in a solvent consisting of 50 vol % ethylene carbonate and 50 vol % diethylene carbonate), the negative electrode plate obtained above, a circular steel plate having a diameter of 13 mm, a spring, and a lid, and was left at room temperature for about 12 hours for stabilization.
[0114] Using the coin battery obtained above, cyclic voltammetry was examined starting from the open circuit potential with an electrochemical measurement system (Biologic, product number: VSP No. 1190) at a potential of 0.1 to 2.1 V, adjusting the scan rate to 0.1 mV / s. The lithium ion diffusion coefficient was determined by examining cyclic voltammetry with the scan rate adjusted to 0.1 mV / s, 0.3 mV / s, 0.5 mV / s, 0.7 mV / s, or 1.0 mV / s.
[0115] The impedance of the coin battery obtained above was examined before and after the cyclic voltammetry. The impedance was examined using an electrochemical measurement system (manufactured by Biologic, product number: VSP No. 1190) equipped with a frequency response analyzer (FRA) in the frequency range of 100 kHz to 10 mHz.
[0116] FIG. 7 shows EIS spectra obtained by measuring impedance before and after cyclic voltammetry measurement using a coin battery using 20 mg of lithium borate-type caffeic acid polymer and 160 mg of graphite. FIG. 7 is a graph showing EIS spectra before and after cyclic voltammetry measurement. Note that "before CV" in FIG. 7 means before cyclic voltammetry measurement, and "after CV" means after cyclic voltammetry measurement. From the results shown in FIG. 7, it can be seen that the impedance of the coin battery is reduced due to a decrease in interfacial resistance after cyclic voltammetry.
[0117] Next, the EIS spectrum was examined when the amount of the lithium borate-type caffeic acid polymer was changed. The results are shown in Figure 8. Figure 8(a) is a graph showing the EIS spectrum before the cyclic voltammetry measurement, and Figure 8(b) is a graph showing the EIS spectrum after the cyclic voltammetry measurement.
[0118] In FIG. 8, A shows the EIS spectrum when the lithium borate type caffeic acid polymer was used in an amount of 2 mg or 8 mg, B shows the EIS spectrum when the lithium borate type caffeic acid polymer was used in an amount of 4 mg, and C shows the EIS spectrum when the lithium borate type caffeic acid polymer was used in an amount of 6 mg.
[0119] The results shown in Figure 8 show that the interfacial resistance increases as the amount of lithium borate-type caffeic acid polymer increases, but as shown by symbol A in Figure 8(a) and symbol A in Figure 8(b), the interfacial resistance is also high when the amount of lithium borate-type caffeic acid polymer is small.
[0120] Next, based on the results of the cyclic voltammetry measurement, the peak potential of delithiation and the lithium ion diffusion coefficient were examined when the amount of the lithium borate type caffeic acid polymer was 2 mg (content: 1 mass%), 6 mg (content: 3 mass%), or 20 mg (content: 10 mass%). As a result, the peak potential of delithiation was 0.18 V when the amount of the lithium borate type caffeic acid polymer was 2 mg, 0.19 V when the amount of the lithium borate type caffeic acid polymer was 6 mg, and 0.23 V when the amount of the lithium borate type caffeic acid polymer was 20 mg. In addition, the lithium ion diffusion coefficient was 1.35×10 when the amount of the lithium borate type caffeic acid polymer was 2 mg. -10 cm 2 / s, and when the amount of lithium borate-type caffeic acid polymer is 6 mg, it is 1.72 × 10 -10 cm 2 / s, and when the amount of lithium borate-type caffeic acid polymer is 20 mg, it is 2.13 × 10 -10 cm 2 From these results, it can be seen that as the content of the lithium borate-type caffeic acid polymer increases, the peak potential of lithium removal increases and the diffusibility of lithium ions improves.
[0121] Next, the charge-discharge cycle characteristics were examined using coin batteries containing 2 mg, 10 mg, or 20 mg of lithium borate-type caffeic acid polymer.
[0122] The charge-discharge cycle characteristics of the coin battery were measured using an automatic battery evaluation device (manufactured by Electrofield Co., Ltd., product number: ABE1024-05RI) and a battery cycler (manufactured by Biologic Co., Ltd., product number: BCS) as charge-discharge devices, with the potential range of 0.1 to 2.1 V (vs. Li / Li + ) and examined at a constant current of 1 C. As the charge / discharge cycle characteristics of the battery, the discharge capacity and charge / discharge efficiency (Coulomb efficiency) were examined when the battery was repeatedly charged and discharged. The results are shown in Figure 9. Figure 9 is a graph showing the measurement results of the discharge capacity and charge / discharge efficiency (Coulomb efficiency) when the coin battery obtained above was repeatedly charged and discharged.
[0123] The term "1C" refers to the current value at which charging and discharging are completed in one hour when a battery cell having a nominal capacity is charged or discharged at a constant current. For example, a current value of 2C means that charging and discharging are completed in two hours.
[0124] In FIG. 9, symbols A to C are graphs showing the measurement results of the discharge capacity, where symbol A is a graph showing the measurement results of the discharge capacity when the amount of the lithium borate type caffeic acid polymer is 2 mg (content: 1 mass%), symbol B is a graph showing the measurement results of the discharge capacity when the amount of the lithium borate type caffeic acid polymer is 6 mg (content: 3 mass%), and symbol C is a graph showing the measurement results of the discharge capacity when the amount of the lithium borate type caffeic acid polymer is 20 mg (content: 10 mass%).
[0125] In addition, in Figure 9, symbols a to c are graphs showing the measurement results of charge / discharge efficiency (Coulombic efficiency), where symbol a is a graph showing the measurement results of charge / discharge efficiency when the amount of lithium borate-type caffeic acid polymer is 2 mg (content: 1 mass%), symbol b is a graph showing the measurement results of charge / discharge efficiency when the amount of lithium borate-type caffeic acid polymer is 6 mg (content: 3 mass%), and symbol c is a graph showing the measurement results of charge / discharge efficiency when the amount of lithium borate-type caffeic acid polymer is 20 mg (content: 10 mass%).
[0126] From the results shown in Figure 9, it can be seen that the discharge capacity of the coin batteries containing 2 mg, 10 mg, or 20 mg of the lithium borate-type caffeic acid polymer was approximately 330 mAh / g even after 10 cycles, indicating that the batteries have excellent charge-discharge cycle characteristics.
[0127] In addition, the measurement results of the charge / discharge cycle and charge / discharge efficiency (the percentage ratio of the discharge capacity during discharge to the charge capacity during charging) of the battery showed that the charge / discharge efficiency of the battery was approximately 100%, indicating that the battery has excellent charge / discharge characteristics. [Industrial Applicability]
[0128] The lithium ion secondary battery negative electrode binder of the present invention and a lithium ion secondary battery in which a negative electrode containing the lithium ion secondary battery negative electrode binder is used provide a lithium ion secondary battery having high ionic conductivity and lithium ion transport number, excellent cycle durability in charge and discharge cycles, and high discharge capacity, and are therefore expected to be used in, for example, smartphones, tablet personal computers, hybrid automobiles, electric automobiles, and the like.
Claims
1. Formula (I): 【Chemistry 1】 [In the formula, R 1 and R 2 each independently represents a hydrogen atom, a hydroxyl group, or an alkyl group having 1 to 4 carbon atoms; R 3 is a hydrogen atom or a group represented by the formula: -OR 4 group (in the formula, R 4 represents a hydrogen atom, an alkyl group having 1 to 6 carbon atoms which may have a halogen atom, or an aryl group having 6 to 12 carbon atoms which may have a halogen atom), A negative electrode binder for a lithium ion secondary battery comprising a lithium borate-type caffeic acid polymer having a repeating unit represented by the formula:
2. A negative electrode for a lithium ion secondary battery comprising the negative electrode binder for a lithium ion secondary battery according to claim 1.
3. A lithium ion secondary battery having a positive electrode, a negative electrode, and a separator disposed between the positive electrode and the negative electrode, wherein the negative electrode is the negative electrode for lithium ion secondary batteries according to claim 2.
4. Formula (I): 【Chemistry 2】 [In the formula, R 1 and R 2 each independently represents a hydrogen atom, a hydroxyl group, or an alkyl group having 1 to 4 carbon atoms; R 3 is a hydrogen atom or a group represented by the formula: -OR 4 group (in the formula, R 4 represents a hydrogen atom, an alkyl group having 1 to 6 carbon atoms which may have a halogen atom, or an aryl group having 6 to 12 carbon atoms which may have a halogen atom), A lithium borate type caffeic acid polymer having a repeating unit represented by the following formula:
5. Formula (II): 【Chemistry 3】 (In the formula, R 1 and R 2 each independently represents a hydrogen atom, a hydroxyl group, or an alkyl group having 1 to 4 carbon atoms. and lithium borohydride in a solution of the formula: R 4 OH (in the formula, R 4 represents a hydrogen atom, an alkyl group having 1 to 6 carbon atoms which may have a halogen atom, or an aryl group having 6 to 12 carbon atoms which may have a halogen atom), 【Chemistry 4】 [In the formula, R 1 and R 2 is the same as above, R 3 is a hydrogen atom or a group represented by the formula: -OR 4 group (in the formula, R 4 represents a group represented by the formula (I) as defined above). A method for producing a lithium borate-type caffeic acid polymer having a repeating unit represented by the formula:
Citation Information
Patent Citations
Battery electrode binder
CN110993948A
Antistatic agent
JP1992252287A
Lithium ion secondary battery, and method for manufacturing the same
JP2012124057A
Polymer, coating agent, ink composition, electricity storage device electrode, and electricity storage device
JP2020015816A
Crosslinked polymeric battery materials
US20180108913A1